The Time of Writing of Kristijonas Donelaitis’ Fables - Dilytė, Dalia (Senoji Lietuvos literatūra, 2014)
Although the versification and language of the fables has never been researched, the existing hypothesis maintains that as their versification and language are of a poorer quality than those of Metai (The Seasons), Donelaitis wrote them at the outset of his creative path. Having decided on verifying this hypothesis, the material of the detailed analysis has demonstrated that the claims regarding the flaws in the versification of the fables are not justified. We can confidently argue that from the point of view of stress versification the hexameters of Donelaitis’ fables are regular and mature. The analysis of the vocabulary of the fables has demonstrated that the fables do not have their own separate lexis. The description and verification of each word has shown that of all the words of different meanings used in the fables only twenty-one words do not appear in The Seasons. In addition, the manner and principles for the use of these words are identical. Therefore, if the vocabulary of The Seasons and that of the fables are essentially the same, then the language of the fables cannot be better or worse than the language of the epic poem. Since we have demonstrated that from the point of view of either versification or vocabulary the fables do not fall behind The Seasons, there is no grounds to claim that the fables are imperfect and were written much earlier than The Seasons. Thus the only aspect that is obvious and true is that we do not know exactly when the fables and The Seasons were written.The analysis presented in this paper would result in the following hypothesis: the fact that the poet uses not only the same words, but also the same word combinations in the fables as in The Seasons, that he follows the same principles of their use shows that the fables are closely linked to The Seasons. In my opinion, Donelaitis wrote the fables at approximately the same time as The Seasons. It is possible that some of the fables were written before embarking on The Seasons, others at the same time as The Seasons, and still others immediately after, there was probably no considerable difference in time between these works.
Keywords: -